Elaboración de diferentes tipos de Hidromiel con saborizantes naturales procedentes de Flores, Frutos y Hojas - Hurtado Lara, Anita Selena (2021)
Honey is a natural sweet substance produced by European bees. (Apis mellifera), also known as the domestic bee, of different subspecies. It is one of the most primitive foods that humans used to use for nourishment, from Prehistory to the present day. The composition of honey is complex and depends on many factors. Like the contribution of plants, climate, soil and environmental conditions. Honey, in addition to being used as a medicinal and nutritional source, is used for the production of a multitude of products such as cosmetics, food products and for the production of fermented beverages such as mead. Mead is one of the first alcoholic beverages originated from the alcoholic fermentation of honey dissolved in water. The same one that is known as one of the oldest drinks in the world that appeared approximately more than 700 years ago in different civilizations such as in India, China, Egypt, Iran and Persia. Which in their times was known as the nectar of their gods. The objective of this work is to make known the importance of the elaboration of mead based on flowers, fruits and leaves, in addition to providing information on the elaboration processes and the protocols that must be followed for its correct elaboration.